Microsoft ADO.NET 4 step by step - Patrick, Tim, 1966-; Safari eBooks (Sebastopol, Calif. : O'Reilly Media, 2010)
Provides tutorials and examples on using ADO.NET 4 to create datacentric applications for Windows and the Web.
Description based on print version record.
Includes index.
Keywords: Microsoft .NET Framework; Microsoft LINQ; Database design; Object-oriented programming (Computer science); Electronic books